1994
DOI: 10.2165/00002512-199405050-00007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Renin-Angiotensin-Aldosterone Axis in Later Life

Abstract: The renin-angiotensin-aldosterone system (RAAS) is one of the main systems involved in the regulation of blood pressure and sodium homeostasis. In animal experiments and in humans, the plasma renin activity and aldosterone levels are reduced with aging. The age-related differences in plasma renin activity and aldosterone are more pronounced in stimulated conditions (when sitting in an upright position, when salt intake is restricted and when plasma volume is depleted) than under basal conditions. Age-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…This is consistent with findings reported by other authors evaluating normotensive subjects (30) and hypertensive patients (31), but it differs from other author's reports (32), where both ALD and PRA were found to decrease with age.…”
Section: Prc Subgroupsupporting
confidence: 92%
“…This is consistent with findings reported by other authors evaluating normotensive subjects (30) and hypertensive patients (31), but it differs from other author's reports (32), where both ALD and PRA were found to decrease with age.…”
Section: Prc Subgroupsupporting
confidence: 92%
“…Furthermore, aging is associated with a reduced adrenal responsiveness to angiotensin II, contributing to lower production of aldosterone and imbalance of sodium homeostasis. 3 We hypothesize that prolonged treatment with KC can normalize the response of glomerulosa to angiotensin II and reverse the clinical picture in some cases of IPA. We did not find any evident cardiovascular alteration in our subjects, even after long-term withdrawal from the therapy, in agreement with a positive effect of aldosterone-receptor blockers to prevent further worsening of this aspect of the disease.…”
Section: Spontaneous Resolution Of Idiopathic Aldosteronism After Lonmentioning
confidence: 96%
“…23 Thus, the current data extend this earlier work in the forearm, demonstrating for the first time a significant increase in AT 1 receptor sensitivity in the leg vasculature of healthy elderly individuals at rest. Although the mechanism for increased AT 1 responsiveness may be as simple as receptor upregulation in response to reduced substrate, 24 this pathway may become an increasingly important regulator of peripheral hemodynamics with advancing age. Recent studies have identified a reduction in postjunctional ␣-adrenergic receptor sensitivity in both the arm 25 and leg of older individuals, 26 yet ␣-adrenergic blockade in this population does not completely restore hemodynamics to that of the young.…”
Section: At 1 Receptor Sensitivity At Restmentioning
confidence: 99%